Atmospheric Humic-Like Substances (HULIS) Act as Ice Active Entities - J. Chen; ZJ Wu; X. Zhao; Wang, Y. J.; Chen, J. C.; Qiu, YT; Zong, T. M.; Chen, H. X.; Wang, B. B.; Lin, P.; Liu, W.; Guo, S.; et al. (Geophysical Research Letters, 2021)
Abstract We investigated the ice nucleation activities of humic-like substances (HULIS), an important component of organic aerosol (OA), derived from atmospheric and biomass burning aerosols, and produced from aqueous-phase chemical reactions. Respective HULIS can effectively trigger heterogeneous IN under mixed-phase cloud conditions. HULIS ice active entities (IAE) were aggregates in size between 0.02 and 0.10 μm. At −20°C, the IAE numbers per unit HULIS mass varied from 213 to 8.7 × 104 mg−1. Such results were different than those detected in aquatic humic substances (HS) from previous studies, implying using HS as surrogates may not robustly estimate the IAE concentrations in the real atmosphere. Combining the abundance of atmospheric HULIS with the present results suggests that HULIS could be an important IAE contributor in the atmosphere where other ice nucleating particle species, such as dust and biological particles, are either low in concentration or absent.